The Influence of Price, Service Quality and Promotion on Customer Satisfaction of Make Up Services at Elma Wedding Nganjuk - Larasati, Dyah Siti Ayu; Meilina, Restin (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: The aim of this research is to analyze the influence of price, service quality and promotion partially and simultaneously on user satisfaction of make-up services at Elma Wedding Nganjuk. Design/Method/Approach: This research uses a quantitative approach and the technique used is causality. The population of this research is all Elma Wedding consumers in 2023 and the sample used in the research was 50 respondents and analyzed using the multiple linear regression method. Research Findings: The results of this research are that the price variable does not have a partially significant effect, but the service quality and promotion variables have a partially significant effect. Price, service quality and promotion simultaneously have a significant influence on customer satisfaction. Theoretical Contribution/Originality: Not much research has discussed the marketing of MUA services. Practical/Policy Implications: Can be useful for marketing make up services. Research Limitations: The limitation of this research is the lack of sampling time because it has entered the rainy season.